Experimental Study of Runoff and Sediment Yield Affected by Ridge Direction and Width of Sloping Farmland - Liu, Shanshan; Qin, Tianling; Lv, Xizhi; Shi, Xuan; Dong, Biqiong; Wang, Jianwei; Liu, Chun (Frontiers in Earth Science, 2021)
Water and soil losses from sloping farmlands potentially contribute to water eutrophication and land degradation. However, few studies explored the combined effects of ridge direction and ridge width on surface runoff and soil losses of sloping farmlands. Twenty-seven experimental plots (8 m long and 4 m wide) with nine treatments (three ridge direction: cross ridge, longitudinal ridge, and oblique ridge; and three ridge width: 40, 60, and 80 cm) were adopted under natural rainfall conditions for two years in the Luanhe River Basin of China. Results indicated that ridge direction had significant effects on runoff and sediment yield (p < 0.05). The ridge width had no significant effect on runoff and sediment yield. No significant interaction effect was found between ridge direction and width on runoff and sediment yield of the sloping farmland based on statistical analyses. Compared with cross-ridge (CR) tillage and oblique-ridge (OR) tillage, longitudinal-ridge (LR) tillage significantly decreased runoff by 78.9% and 64.9% and soil losses by 88.2 and 83.5%, respectively (p < 0.05). The effects of ridge directions on runoff and sediment yield were related to rainfall grade. When the rainfall grade reached rainstorm, the runoff yield under CR, LR, and SR had significant differences (p < 0.05). The runoff under LR and OR treatment was 5.16 and 3.3 times, respectively, of that under CR. When the rainfall level was heavy rain or rainstorm, the sediment yield under LR was significantly greater than that under CR. The sediment yield was 13.45 times of that under CR. Cross-ridge tillage with a ridge width of 40 cm is an optimally effective measure of soil and water conservation on sloping farmland in arid and semiarid regions of China.